History. Grade 11 - Rogers. A; Rogers, A; Ellis, P; Olivier, P (Pietermaritzburg : Shuter & Shooter, 2017)
History grade 11 detailed content and a focus on sources and context ensure that you have a thorough understanding of historical events. The ability to contrast and compare, and analyse and describe the events of history are a key component of your history grade 11 examination.
Keywords: History Problems, exercises, etc